A discursive construction of resistance in police-suspect interactions in Ibadan, Nigeria. Issue 4 (2nd October 2021) - Akinrinlola, Temidayo
Abstract: Police-suspect interactions (PSIs) are a site for negotiating power. In the Nigerian context, scholarly investigations from the pragmatic and discourse analytical ambits have probed how investigating police officers (IPOs) enact and sustain power in PSIs. However, the place of the suspect in Nigerian policing has not enjoyed sufficient scholarly investigation. This study investigates how suspects deploy discursive devices to resist IPOs' powers, with a view to describing the implication of such resistance for the language of interrogation in Ibadan, Nigeria. Fairclough's perspective on power relations serves as the theoretical anchor for the study. Twenty interrogation sessions were audio recorded at the State Criminal Investigation and Intelligence Department (SCIID), Ìyágankú, Ibadan, Oyo State. Of these, eight interrogation sessions, two cases each of kidnapping, affray, conspiracy and defamation of character were selected for analysis. The analysis of selected data reveals that suspects are not usually at the mercy of IPOs during PSIs; they resist police powers by deploying topic control to construct avoidance, positive self, denial through alternatives, concealment and interrogatives to challenge IPOs so as to avoid incrimination. The study recommends further suspect-related studies to further establish the place of the suspect in PSIs.